Taste receptors in asthma. Issue 1 (February 2015) - Grassin-Delyle, Stanislas; Naline, Emmanuel; Devillier, Philippe
<x xml:space="preserve">Abstract</x> Purpose of review Although today's cornerstone therapies for asthma (inhaled bronchodilators and corticosteroids) target airway narrowing and lung inflammation, about half of treated asthmatic patients do not achieve good disease control. There is a clear need for new therapeutic approaches and novel drug targets. Recent research has unexpectedly revealed that certain taste receptors (particularly those involved in bitter taste transduction) are expressed in lung tissue. Recent findings Bitter taste receptors are expressed in several cell types in the lungs (such as chemosensory cells, epithelial cells, smooth muscle cells, lymphocytes, and macrophages) and variously involved in ciliary beating, muscle relaxation, and/or inhibition of the production of inflammatory mediators. Here, we review recent research on the role of bitter taste receptors in experimental models of asthma and in asthmatics. Summary The currently available data suggest that bitter taste receptor agonists have therapeutic potential in chronic obstructive airway diseases such as asthma.